EFFECT OF BODY CONDITION SCORE AND FERTILITY STATUS ON PROTEINS AND MICRO-MINERALS PROFILE OF ESTRUAL MUCUS IN GIR COWS - GOHEL, M M; KAVANI, F S; HADIYA, K K (The Indian Journal of Animal Reproduction, 2023)
A total fifty Gir cows of different reproductive status ( 1 O=normal cyclic, 20=repeat breeders and 20=i nduced estrus) were selected to determine total proteins and micro-minerals profile in their estrual cervico-vaginal mucus (CVM) in relation to body condition score (on 0-5 point scale) and fertility post-Al. The overall mean concentrations of total protein (g/dl) and micro-minerals, viz, copper, iron, zinc and manganese (ppm) in CVM of these cows were 3.48±0. 04, 0 .90±0. 06, 9. 78±0.38, 1. 02±0. 04 and 1. 75±0.10, respectively. Total protein content of CVM was neither influenced by groups, conception nor body condition score (BCS). The concentrations of copper and manganese were significantly lower (P<0.01) and those of zinc and iron apparently lower in repeat breeding cows than in normal cyclic and induced estrus cows. The levels of all four mineral elements were signifiantly higher in CVM of conceived than non-conceived cows. However, there was no any specific trend between levels of these constituents in CVM and BCS of cows of any group, though a trend of decreasing levels with increasing BCS was noted in copper and zinc, and the levels of copper and manganese were high in cows with BCS 3.0 and 3.5, respectively. The results indicated that the micro-minerals deficit in CVM could be the cause of conception failure in repeat breeding cows.